Ask Question
29 January, 15:39

How to solve 4 (7-3x) = 7 (4-2x)

+3
Answers (2)
  1. 29 January, 16:57
    0
    Step-by-step explanation:

    First, you distribute the 4 and 7 to the stuff inside the parentheses 28 - 12x = 28 - 14x then add 28 to both sides - 12x = - 14x then add 14x to both sides 2x = 0 then divide both sides by 2 x = 0
  2. 29 January, 17:16
    0
    x=0

    Step-by-step explanation:

    4 (7-3x) = 7 (4-2x)

    Distribute

    28 - 12x = 28 - 14x

    Subtract 28 from each side

    -12x = - 14x

    Add 14x to each side

    -12x+14x = - 14x+14x

    2x=0

    x = 0
Know the Answer?